Ramanujan found the following trigonometric identity \begin{equation} \sqrt[3]{\cos\bigl(\tfrac{2\pi}7\bigr)}+ \sqrt[3]{\cos\bigl(\tfrac{4\pi}7\bigr)}+ \sqrt[3]{\cos\bigl(\tfrac{8\pi}7\bigr)}= \sqrt[3]{\tfrac{5-3\sqrt[3]7}2} \end{equation} (see e.g. Ramanujan — For Lowbrows, (3.7) and around, for details and an analogue for 9 instead of 7).

Are there analogous identities for all primes $p$ of the form $3k+1$ instead of 7?

Let me try to explain what I mean. As I've learned from S. Markelov, for $p=13$ \begin{multline} \sqrt[3]{\cos\bigl(\tfrac{2\pi}{13}\bigr)+\cos\bigl(\tfrac{10\pi}{13}\bigr)}+ \sqrt[3]{\cos\bigl(\tfrac{4\pi}{13}\bigr)+\cos\bigl(\tfrac{6\pi}{13}\bigr)}+ \sqrt[3]{\cos\bigl(\tfrac{8\pi}{13}\bigr)+\cos\bigl(\tfrac{12\pi}{13}\bigr)}=\\ \sqrt[3]{\tfrac{3\sqrt[3]{13}-7}2} \end{multline} and there are close analogues for all $p$ of the form $n^2+n+1$. For example, for $p=43=6^2+6+1$ three groups of numerators are {2, 4, 8, 16, 22, 32, 42}, {6, 10, 12, 20, 24, 38, 40}, {14, 18, 26, 28, 30, 34, 36} and the sum is $\sqrt[3]{\frac{3\sqrt[3]{86}-13}2}$.

So it looks like there is some pattern reminding of... quadratic Gauss sums, perhaps.

For any $p=3k+1$ one can partition $\mathbb F_p^\times$ into three groups, corresponding to $\mathbb F_p^\times/\mathbb F_p^{\times3}\cong\mathbb Z/3$ — and this is precisely the partitions from the last paragraph. This explains what LHS should look like. And indeed, at least for $p=19$ there is an identity \begin{multline} \sqrt[3]{\cos\bigl(\tfrac{\pi}{19}\bigr)+\cos\bigl(\tfrac{7\pi}{19}\bigr)+\cos\bigl(\tfrac{11\pi}{19}\bigr)}+ \sqrt[3]{\cos\bigl(\tfrac{3\pi}{19}\bigr)+\cos\bigl(\tfrac{5\pi}{19}\bigr)+\cos\bigl(\tfrac{17\pi}{19}\bigr)}+\\ \sqrt[3]{\cos\bigl(\tfrac{9\pi}{19}\bigr)+\cos\bigl(\tfrac{13\pi}{19}\bigr)+\cos\bigl(\tfrac{15\pi}{19}\bigr)}=\\ \sqrt[3]{\tfrac12-3\sqrt[3]7+\tfrac32\sqrt[3]{3\sqrt[3]{49}+18\sqrt[3]7-25}+\tfrac32\sqrt[3]{3\sqrt[3]{49}+18\sqrt[3]7-44}} \end{multline} which is closely related to the fact that $2 \left( \cos \frac{4\pi}{19} + \cos \frac{6\pi}{19}+\cos \frac{10\pi}{19} \right)$ is a root of the equation $\sqrt{ 4+ \sqrt{ 4 + \sqrt{ 4-x}}}=x$.


more precisely: is it true, that for any $p=3k+1$ the sum of 3 cubic roots of sum of cosines (described above) can be expressed in real radicals?

what can be said about RHS in this case (say, about the number of nested radicals)?

  • 1
    $\begingroup$ (Answers to more informal question just what's going on here? would also be appreciated.) $\endgroup$ – Grigory M Jan 19 '14 at 18:30
  • 1
    $\begingroup$ Related : math.stackexchange.com/questions/612607/… $\endgroup$ – lab bhattacharjee Jan 20 '14 at 5:46
  • 1
    $\begingroup$ @GrigoryM: The thingie with $\cos(\pi/19)$ can be generalized. Kindly see this post. $\endgroup$ – Tito Piezas III Dec 13 '14 at 5:16
  • 1
    $\begingroup$ A lot of neat stuff here. I upvoted everybody. $\endgroup$ – marty cohen Jun 27 '16 at 15:20
  • 1
    $\begingroup$ @GrigoryM: Noam Elkies has finally found an analogous quintic that uses $\cos \pi/11$. See this MO post. $\endgroup$ – Tito Piezas III Aug 2 '16 at 19:21


The question is: Is it true, that for any $p=3k+1$ the sum of 3 cubic roots of sum of cosines can be expressed in real radicals?

The answer is Yes. In general, given the roots $x_i$ of the general cubic equation,


then sums involving the cube roots of the $x_i$ can be given in the simple form,

$$(u+x_1)^{1/3}+(u+x_2)^{1/3}+(u+x_3)^{1/3} = \big(w+3\,\sqrt{d}\,^{1/3}\big)^{1/3}$$

where $u,w$ are the constants,

$$u = \frac{ab-9c+\sqrt{d}}{2(a^2-3b)}$$

$$w = -\frac{(2a^3-9ab+27c)+9\sqrt{d}}{2(a^2-3b)}$$

and $d$ is the negated discriminant $D$,

$$d = -D = \tfrac{1}{27}\Bigl(4(a^2-3b)^3-(2a^3-9ab+27c)^2\Bigr)$$

  1. If $d$ is positive, meaning the discriminant $D$ is negative, so the cubic has all real roots, thus $u,w$ are also real.
  2. Furthermore, if the cubic has a cyclic group, which is the case when it involves the $p$th root of unity, then $d$ is a square, so $u,w$ in fact are rational.
  3. The case $a^2-3b=0$ implies $d =-(a^3-27c)^2$, so $+D$, hence only one root $x_1$ is real.

Example. If we use the cubic for $\cos(2\pi/7)$, namely $x^3 + x^2 - 2x - 1 = 0$, then we have either $u = 0$ or $1$, since $\pm\sqrt{d} = 7$. So using the negative and positive case respectively, we get,

$$\sqrt[3]{2\cos\bigl(\tfrac{2\pi}{7}\bigr)}+\sqrt[3]{2\cos\bigl(\tfrac{4\pi}{7}\bigr)}+\sqrt[3]{2\cos\bigl(\tfrac{8\pi}{7}\bigr)} = \sqrt[3]{5\color{blue}{-}3\,\sqrt[3]{7}}$$

$$\sqrt[3]{1+2\cos\bigl(\tfrac{2\pi}{7}\bigr)}+\sqrt[3]{1+2\cos\bigl(\tfrac{4\pi}{7}\bigr)}+\sqrt[3]{1+2\cos\bigl(\tfrac{8\pi}{7}\bigr)} = \sqrt[3]{-4\color{blue}{+}3\,\sqrt[3]{7}}$$

and so on for other $p=6m+1$, covering my old addendum for $p=19$.

$\color{brown}{Old\; answer:}$

The general phenomenon can be explained by a beautiful cubic identity found by, of course, Ramanujan. {Grigori M, ironically, you pointed out this identity in an old question of mine. :) }

I. Given the three roots $x_i$ of,

$$x^3-ax^2+bx-1 = 0\tag1$$


$$x_1^{1/3}+x_2^{1/3}+x_3^{1/3} = (a+6+3t)^{1/3}\tag2$$

where $t$ is a root of,

$$t^3-3(a+b+3)t-\big(ab+6(a+b)+9\big) = 0\tag3$$

The form of the $p=19$ suggests it is just a particular case of this identity. Note that,


(and the other two similar expressions) is a root of,


One can then scale variables and make the constant term $c=-1$. I did so, and got the exact form as the one above.

II. Note that if $a+b+3=0$, then $(3)$ takes a particularly simple form. After some manipulation, I found that given,

$$x^3 + x^2 - (3 n^2 + n)x + n^3=0\tag4$$


$$F_P = x_1^{1/3}+x_2^{1/3}+x_3^{1/3} = \sqrt[3]{-(6n+1)+3\sqrt[3]{nP}}\tag5$$

where $P = 9n^2+3n+1$. For $n = -1, 1, -2, 2$, we get the same cubics satisfied by the sums of cosines for $P=7,13,31,43,\dots$ thus explaining the simple sums,

$$F_7 =-\sqrt[3]{-5+3\sqrt[3]{7}} $$

$$F_{13} = \sqrt[3]{-7+3\sqrt[3]{13}} $$

and so on, though I cannot prove that the roots of $(4)$ are always sums of cosines when $P$ is prime. Maybe I'll ask it as a separate question.

  • $\begingroup$ @GrigoryM: I've now asked the question here. $\endgroup$ – Tito Piezas III Dec 14 '14 at 19:30
  • $\begingroup$ I actually used the cubic for $p=19$ and got the same result as the guy from artofproblemsolving. Since the cubic is $y^3+y^2-6y-7=0$, you have to scale it by $y = 7^{1/3}x$ which explains the 3rd level of cube roots. I'm 100% sure he used Ramanujan's identity, but didn't tell, tsk, tsk. $\endgroup$ – Tito Piezas III Dec 14 '14 at 20:59
  • $\begingroup$ Thank you. I need to think about it for some time. $\endgroup$ – Grigory M Dec 14 '14 at 21:34
  • $\begingroup$ One note, if $a^2 - 3b = 0$, then the cubic $x^3 + ax^2 + bx + c$ can be written as $x^3 + 3\frac{a}{3}x^2 + 3\left(\frac{a}{3}\right)^2 x + \left(\frac{a}{3}\right)^3 + c - \left(\frac{a}{3}\right)^3$, and that means your cubic is just $(x-h)^3 + k$ for appropriate $h,k$. $\endgroup$ – Gregory Dresden Aug 22 '17 at 3:00
  • $\begingroup$ @TitoPiezasIII, I have some other comments & questions but I'll send them to you in an email. $\endgroup$ – Gregory Dresden Aug 22 '17 at 3:06

$\color{blue}{\text{Edited 9 Jun 2017:}}$

Let $p$ be a prime number congruent to 1 modulo 6, and $g$ a primitive root modulo $p$, i.e. a generator of the group $ \mathbb F_{p} ^ {\times} \cong C_{p-1} $. By definition, put $$ S_p(g) = \sum_{k=0}^{\frac{p-4}3}\cos \left(\frac{2\pi}{p}g^{3k}\right) , S'_p(g) =\sum_{k=0}^{\frac{p-4}3}\cos \left(\frac{2\pi}{p}g^{3k+1}\right) \text{, } S''_p(g) = \sum_{k=0}^{\frac{p-4}3}\cos \left(\frac{2\pi}{p}g^{3k+2}\right) . $$

In this PDF we prove the following result.

Theorem 1. Suppose $p$ equals $9m^2+3m+1$ for some $m\in \mathbb Z$. Then for any primitive root $g$ we have $$\sqrt[3]{S_p(g)} + \sqrt[3]{S'_p(g)} + \sqrt[3]{S''_p(g)} =\sqrt[3]{ 3\sqrt[3]{mp}-(6m+1) } . $$

Warning: I am not sure about my English. If you find some mistakes please write me.


I tried to find such rationals $a,b,c,d$ so that, $$(a+b\,x_1)^{1/3} + (a+b\,x_2)^{1/3} + (a+b\,x_3)^{1/3} = (c+\sqrt[3]{dp})^{1‌​/3}$$ So, we have identities for all primes $p=1\ mod\ 3$ such that $p<100$ $$\sqrt[3]{1+\sum_{k=0}^{5}\cos(\frac{2\pi }{19}\cdot2^{3k}) }+\sqrt[3]{1+\sum_{k=0}^{5}\cos(\frac{2\pi }{19}\cdot2^{3k+1}) }+\sqrt[3]{1+\sum_{k=0}^{5}\cos(\frac{2\pi }{19}\cdot2^{3k+2}) }=\sqrt[3]{8-3\sqrt[3]{19}}\qquad\\ \sqrt[3]{-1+\sum_{k=0}^{11}\cos(\frac{2\pi }{37}\cdot2^{3k}) }+\sqrt[3]{-1+\sum_{k=0}^{11}\cos(\frac{2\pi }{37}\cdot2^{3k+1}) }+\sqrt[3]{-1+\sum_{k=0}^{11}\cos(\frac{2\pi }{37}\cdot2^{3k+2}) }=\sqrt[3]{-10+3\sqrt[3]{37}}\qquad\\ \sqrt[3]{-1+\sum_{k=0}^{19}\cos(\frac{2\pi }{61}\cdot2^{3k}) }+\sqrt[3]{-1+\sum_{k=0}^{19}\cos(\frac{2\pi }{61}\cdot2^{3k+1}) }+\sqrt[3]{-1+\sum_{k=0}^{19}\cos(\frac{2\pi }{61}\cdot2^{3k+2}) }=\sqrt[3]{14-3\sqrt[3]{3\cdot 61}}\qquad\\$$

$$\sqrt[3]{1+\sum_{k=0}^{21}\cos(\frac{2\pi }{67}\cdot2^{3k}) }+\sqrt[3]{1+\sum_{k=0}^{21}\cos(\frac{2\pi }{67}\cdot2^{3k+1}) }+\sqrt[3]{1+\sum_{k=0}^{21}\cos(\frac{2\pi }{67}\cdot2^{3k+2})}=\sqrt[3]{-16+3\sqrt[3]{3\cdot 67}}\qquad\\ \sqrt[3]{-2+\sum_{k=0}^{25}\cos(\frac{2\pi }{79}\cdot3^{3k}) }+\sqrt[3]{-2+\sum_{k=0}^{25}\cos(\frac{2\pi }{79}\cdot3^{3k+1})}+\sqrt[3]{-2+\sum_{k=0}^{25}\cos(\frac{2\pi }{79}\cdot3^{3k+2})}=\sqrt[3]{-13+3\sqrt[3]{79}}\qquad\\ \sqrt[3]{3+\sum_{k=0}^{31}\cos(\frac{2\pi }{97}\cdot5^{3k}) }+\sqrt[3]{3+\sum_{k=0}^{31}\cos(\frac{2\pi }{97}\cdot5^{3k+1})}+\sqrt[3]{3+\sum_{k=0}^{31}\cos(\frac{2\pi }{97}\cdot5^{3k+2})}=\sqrt[3]{14-3\sqrt[3]{97}} $$

$\color{blue}{\text{Added June 27:}}$

$$\sqrt[3]{\frac{74}{43}+\sum_{k=0}^{1}\cos(\frac{2\pi }{7}\cdot3^{3k}) }+\sqrt[3]{\frac{74}{43}+\sum_{k=0}^{1}\cos(\frac{2\pi }{7}\cdot3^{3k+1}) }+\sqrt[3]{\frac{74}{43}+\sum_{k=0}^{1}\cos(\frac{2\pi }{7}\cdot3^{3k+2}) }=\sqrt[3]{\frac{392}{43}}$$ $$\sqrt[3]{\frac{5105}{11349}+\sum_{k=0}^{1}\cos(\frac{2\pi }{7}\cdot3^{3k}) }+\sqrt[3]{\frac{5105}{11349}+\sum_{k=0}^{1}\cos(\frac{2\pi }{7}\cdot3^{3k+1}) }+\sqrt[3]{\frac{5105}{11349}+\sum_{k=0}^{1}\cos(\frac{2\pi }{7}\cdot3^{3k+2}) }=\sqrt[3]{\frac{21}{1261}}$$ $$\sqrt[3]{-\frac{2306997866696}{1047656140569}+\sum_{k=0}^{1}\cos(\frac{2\pi }{7}\cdot3^{3k}) }+\sqrt[3]{-\frac{2306997866696}{1047656140569}+\sum_{k=0}^{1}\cos(\frac{2\pi }{7}\cdot3^{3k+1}) }+\sqrt[3]{-\frac{2306997866696}{1047656140569}+\sum_{k=0}^{1}\cos(\frac{2\pi }{7}\cdot3^{3k+2}) }=-\sqrt[3]{\frac{118149192000}{1908298981}}$$ $$\sqrt[3]{\frac{9658771264742899051}{5361029308457632889}+\sum_{k=0}^{1}\cos(\frac{2\pi }{7}\cdot3^{3k}) }+\sqrt[3]{\frac{9658771264742899051}{5361029308457632889}+\sum_{k=0}^{1}\cos(\frac{2\pi }{7}\cdot3^{3k+1}) }+\sqrt[3]{\frac{9658771264742899051}{5361029308457632889}+\sum_{k=0}^{1}\cos(\frac{2\pi }{7}\cdot3^{3k+2}) }=\sqrt[3]{\frac{60079542508626277}{3881990809889669}}$$ $$\sqrt[3]{\frac{1512950552654226074845360221799154}{22816093930106873589073278570630913}+\sum_{k=0}^{1}\cos(\frac{2\pi }{7}\cdot3^{3k}) }+\sqrt[3]{\frac{1512950552654226074845360221799154}{22816093930106873589073278570630913}+\sum_{k=0}^{1}\cos(\frac{2\pi }{7}\cdot3^{3k+1}) }+\sqrt[3]{\frac{1512950552654226074845360221799154}{22816093930106873589073278570630913}+\sum_{k=0}^{1}\cos(\frac{2\pi }{7}\cdot3^{3k+2}) }=-\sqrt[3]{\frac{9567191523845032860388297048}{16721690052047565734068821733}}$$ and so on.

  • $\begingroup$ I already gave the general formula as $$ (u+x_1)^{1/3} + (u+x_2)^{1/3} + (u+x_3)^{1/3} = (w+3\sqrt{d}\,^{1/3})^{1‌​/3}$$ where the $x_i$ are the roots of the cubic and $u,w$ are in terms of the coefficients. See answer above. But these explicit relations are also nice. $\endgroup$ – Tito Piezas III Jan 5 '16 at 18:16
  • $\begingroup$ I didn't use this formula because it gives only one solution.I think there are two identities for any $p$ but I can't proove it. For example: $$\sqrt[3]{1+\sum_{k=0}^{5}\cos(\frac{2\pi }{19}\cdot2^{3k}) }+\sqrt[3]{1+\sum_{k=0}^{5}\cos(\frac{2\pi }{19}\cdot2^{3k+1}) }+\sqrt[3]{1+\sum_{k=0}^{5}\cos(\frac{2\pi }{19}\cdot2^{3k+2}) }=\sqrt[3]{8-3\sqrt[3]{19}}\qquad \sqrt[3]{2+\sum_{k=0}^{5}\cos(\frac{2\pi }{19}\cdot2^{3k}) }+\sqrt[3]{2+\sum_{k=0}^{5}\cos(\frac{2\pi }{19}\cdot2^{3k+1}) }+\sqrt[3]{2+\sum_{k=0}^{5}\cos(\frac{2\pi }{19}\cdot2^{3k+2}) }=\sqrt[3]{-1+3\sqrt[3]{19}}\qquad$$ $\endgroup$ – davidoff303 Jan 9 '16 at 16:30
  • $\begingroup$ The formula actually gives two solutions by using $\pm\sqrt{d}$. In fact, I gave two solutions in the example in my answer, one for $+\sqrt{7}$ and the other for $-\sqrt{7}$. $\endgroup$ – Tito Piezas III Jan 9 '16 at 20:57
  • $\begingroup$ You are right, I was inattentived. I solved some diophantine equation and my solutions are equal yours. $\endgroup$ – davidoff303 Jan 10 '16 at 8:03
  • $\begingroup$ Do you think you can find anything if there is a $5$th power version, $$(u+x_1)^{1/5}+(u+x_2)^{1/5}+\dots+(u+x_5)^{1/5} = (p+q\sqrt[5]{d})^{1/5}$$ $\endgroup$ – Tito Piezas III Jan 10 '16 at 12:11

Suppose $p=3k+1$. Then by a theorem of Gauss $4p=A^2+27B^2$ and cubic sums like $\displaystyle\sum_{t\in\mathbb Z/p}\cos\left(\frac{2\pi t^3}p\right)$ are roots of the equation $x^3-3px-Ap=0$. And if we have three roots $x_i$ of a cubic equation, Ramanujan's lemma gives the value of $\sqrt[3]{x_1}+\sqrt[3]{x_2}+\sqrt[3]{x_3}$. That's precisely what's going on, I believe.

  • $\begingroup$ I'll try to expand this answer later $\endgroup$ – Grigory M Jan 3 '15 at 23:44
  • $\begingroup$ Related: upd. in math.stackexchange.com/q/102736 and math.stackexchange.com/a/31600 $\endgroup$ – Grigory M Jan 3 '15 at 23:48
  • 1
    $\begingroup$ Ramanujan's lemma works for any cubic eqn. However, I'm suspecting that for prime $p=3m+1$ where the roots $x_i$ involve the $p$th root of unity thus are sums of cosines, then I think one can always find rationals $a,b,c,d$ to the identity, $$(a+b\,x_1)^{1/3}+(a+b\,x_2)^{1/3}+(a+b\,x_3)^{1/3}=\big(c+\sqrt[3]{dp}\big)^{1/3}$$ There is a family of $p$ where $a=0$, and Ramanujan's $p=7$ was the simplest. $\endgroup$ – Tito Piezas III Jan 3 '15 at 23:55

(Addendum to my answer.) I just realized that given the $p=19$ identity cited by the OP,

$$\sqrt[3]{\cos\bigl(\tfrac{\pi}{19}\bigr)+\cos\bigl(\tfrac{7\pi}{19}\bigr)+\cos\bigl(\tfrac{11\pi}{19}\bigr)}+\\ \sqrt[3]{\cos\bigl(\tfrac{3\pi}{19}\bigr)+\cos\bigl(\tfrac{5\pi}{19}\bigr)+\cos\bigl(\tfrac{17\pi}{19}\bigr)}+\\ \sqrt[3]{\cos\bigl(\tfrac{9\pi}{19}\bigr)+\cos\bigl(\tfrac{13\pi}{19}\bigr)+\cos\bigl(\tfrac{15\pi}{19}\bigr)}=\\ \sqrt[3]{\tfrac12-3\sqrt[3]7+\tfrac32\sqrt[3]{3\sqrt[3]{49}+18\sqrt[3]7-25}+\tfrac32\sqrt[3]{3\sqrt[3]{49}+18\sqrt[3]7-44}}=0.815731\dots$$

a small tweak can give a simpler, but different one,

$$\sqrt[3]{ -\tfrac{1}{2}+\cos\bigl(\tfrac{\pi}{19}\bigr)+\cos\bigl(\tfrac{7\pi}{19}\bigr)+\cos\bigl(\tfrac{11\pi}{19}\bigr)}+\\ \sqrt[3]{-\tfrac{1}{2}+\cos\bigl(\tfrac{3\pi}{19}\bigr)+\cos\bigl(\tfrac{5\pi}{19}\bigr)+\cos\bigl(\tfrac{17\pi}{19}\bigr)}+\\ \sqrt[3]{-\tfrac{1}{2}+\cos\bigl(\tfrac{9\pi}{19}\bigr)+\cos\bigl(\tfrac{13\pi}{19}\bigr)+\cos\bigl(\tfrac{15\pi}{19}\bigr)}=\\ \sqrt[3]{-4+\tfrac{3}{2}\sqrt[3]{19}}=0.1375504\dots$$

It's because there is only a linear transformation between the cubic involved in,

$$\sqrt{ a+ \sqrt{ a + \sqrt{ a-x}}}=x$$

and the cubic for,

$$y_1^{1/3}+y_2^{1/3}+y_3^{1/3} = \sqrt[3]{-(6n+1)+3\sqrt[3]{nP}}$$

with $P = 9n^2+3n+1$, and we use $n=\frac{1}{2}$.

See these comments.

  • $\begingroup$ haha $n = 1/2$ ? so that's what breaks the integral normal basis thing and get you those $-1/2$ constant coefficient ? $\endgroup$ – mercio Dec 31 '14 at 5:23
  • $\begingroup$ @mercio: I'm still not sure how to get those constants in front of the cosines in the other post, but this one works. :) $\endgroup$ – Tito Piezas III Dec 31 '14 at 5:29
  • $\begingroup$ wait... those two identities are different right ? why do you say it's a simplification ? this looks crazy anyway... $\endgroup$ – mercio Dec 31 '14 at 5:37
  • $\begingroup$ @mercio: Yes, they are different. I was being imprecise. I'll edit and phrase it another way. $\endgroup$ – Tito Piezas III Dec 31 '14 at 5:43

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.